Case report: 3D intracranial vessel wall MRI in Susac syndrome: potential relevance for diagnosis and therapeutic management - Lotti, Antonio; Barilaro, Alessandro; Mariottini, Alice; Vannozzi, Lorenzo; Piergentili, Marco; Fainardi, Enrico; Massacesi, Luca (Frontiers in Neurology, 2023)
Susac syndrome (SS) is a rare immune-mediated vasculitis affecting retina, inner ear and brain. Assessment of central nervous system (CNS) involvement is currently based on standard brain magnetic resonance imaging (MRI) sequences. Accuracy of three dimensional (3D)-vessel wall imaging (VWI) was compared to standard sequences and contrast-enhanced-3D T2-fluid attenuated inversion recovery (CE-FLAIR) to assess CNS disease activity in two cases of definite SS. Brain MRI scan and retinal fluorescein angiogram (RFA) were performed at disease onset and at one, three and six months after induction therapy start. CE-FLAIR and VWI based on 3D black-blood proton density weighted (PDW) with and without gadolinium were added to standard sequences on a 3 Tesla MRI scanner. Contrast enhanced-VWI (CE-VWI) detected an abnormal diffuse leptomeningeal enhancement (LME) in both cases at onset and during follow-up. Pathological enhancement on CE-VWI persisted at six-month brain MRI, despite absence of new lesions and disappearance of LME on CE-FLAIR. Follow-up RFA revealed new arterial wall hyperfluorescence in both cases. VWI may represent a useful tool for diagnosing and monitoring CNS disease activity in SS patients, as confirmed by concordance with RFA, leading treatment’s choice and timing. Moreover, CE-VWI seemed at least as sensitive as CE-FLAIR in detecting LME, possibly being superior to the latter in posterior fossa. LME remission might be not accurate in predicting suppression of CNS inflammation in SS.